BROWNFIELD INVESTMENTS AS POSSIBILITY OF REVITALIZATION AND SUSTAINABILITY OF LOCATIONS - Sredojević, Zorica; Kljajić, Nataša; Gajić, Boško (Economics of Agriculture, 2019)
Investments for revitalization of locations through Brownfield investments provide an opportunity to establish and test new sustainable development practices. The economic advantage of analyzed Brownfield investments is that there are already certain capacities and infrastructure in a specific location. The research found that the funds invested in the cleaning of the terrain, waste treatment with the so-called. "Wild" landfills, in adaptation of buildings, arrangement of green areas, improvement of infrastructure and the like, have economic and financial justification. In addition, a number of other qualitative effects of general interest have been highlighted. The effects of this investment are considered from socioeconomic, environmental and other aspects, as well as to the development of local economy and environmental protection. In addition to the ecological and economic aspects of investing in Brownfield investment, special attention should be paid to risk management and social aspects of local sustainable development.